Behavioural and social problems exhibited by students with learning disabilities in Ibadan North Local Government Area, Oyo State (2014)
This paper investigated the perceived behavioural problems (emotional, conduct, hyperactivity/inattention), and social problems (peer relationship and pro-social difficulties) as presented by students with learning disabilities in Ibadan North Local Government Area, of Oyo State. Descriptive research design of ex-post facto type was adopted. An Adopted Strengths and Difficulties Questionnaire (SDQ) (r =0.71) was used to collect data far the study. A total of one hundred and four (104) Junior Secondary School Classes 1-3 students with learning disabilities comprising (males = 62, and females 42) with age range between ll-16years were purposively selected using the Pupils Rating Scale (r= 0.90). Percentages were used to analyse demographic Information while inferential statistics of Chi-Square was used to answer five research questions at 0.05 level of significance. The results showed that students with learning disabilities significantly perceived that emotional problems (X(2) cal=26.96, X(2) crit.=18.307 df 10, p<0.05) conduct problems (X(2) cal=62.481, X(2) crit.=18.307 df 10, p<0.05); hyperactivity/inattention problems (X(2) cal=67.865, X(2) crit.=12.59 df 6, , p<0.05); peer relationship problems (X(2) cal=54.154, X(2) crit.=12.59df 6, = P<0.05); and pro-social difficulties (X(2) cal=50.808 X(2) crit.=15.507df 8, p<0.05), are behavioural and social problems exhibited by students with learning disabilities. It was recommended that teachers of students with learning disabilities. both regular and special teachers should endeavour to understand and address behavioural and social problems of students with learning disabilities. Teachers should ensure that they do not exacerbate behavioural and social problems as these can contribute to lowered academic achievement. They should be proactive and ready to remediate these problems whenever necessary.